Development of a vegetable slicing machine / Adil Ariff and Mohd Fadzli Ismail - Ariff, Adil; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2023)
Nowadays, there are many people who are still using manual cutting vegetable method which is chopping and slicing by using hand knives. The manual method of chopping and slicing vegetables using hand knives is time-consuming and dangerous, as it exposes the hands to sharp blades. This project aims to design and fabricate a low-cost and portable vegetable slicing machine to ease the workload of housewives. The machine had been designed using SolidWork and successfully fabricated. The machine utilized a direct current motor to move the cutting blade, ensuring portability and ease of use. The frame is made of lightweight aluminium profile, making it easy to handle and transport. In addition, the design of the machine also focused on safety features to avoid injuries. The machine was covered with acrylic to ensure the safety of users and for aesthetics purpose. The result showed that this project improved the quality of life for housewives by reducing the time and effort required to chop and slice vegetables manually.